Speech processing and soft computing - Selouani, Sid-Ahmed (SpringerBriefs in Electrical and Computer Engineering, 2011)
Speech Processing and Soft Computing includes coverage of synergy between speech technology and bio-inspired soft computing methods. Through practical cases, the author explores, dissects and examines how soft computing may complement conventional techniques in speech enhancement and speech recognition in order to provide robust systems. The material is especially useful to graduate students and experienced researchers who are interested in expanding their horizons and investigating new research directions through review of the theoretical and practical settings of soft computing methods in very recent speech applications.